Die opkoms van die menseregte-ideologie en enkele begeleidingsimplikasies daarvan - Niekerk, E. J. van (Koers, 1996)
The rise of the human rights ideology and its implications for accompanimentSince the Renaissance several developments have contributed to the rise and the eventual consolidation of the currently popular human rights ideology. In this article three of these developments are discussed, namely the advent of a developed societal dispensation, the advent of a globalistic societal dispensation and the advent of a secularistic societal dispensation. From this historical investigation several general implications of the human rights ideology for the South African educational context are indicated inferred.